6x-(3x+7)=27

Simple and best practice solution for 6x-(3x+7)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-(3x+7)=27 equation:


Simplifying
6x + -1(3x + 7) = 27

Reorder the terms:
6x + -1(7 + 3x) = 27
6x + (7 * -1 + 3x * -1) = 27
6x + (-7 + -3x) = 27

Reorder the terms:
-7 + 6x + -3x = 27

Combine like terms: 6x + -3x = 3x
-7 + 3x = 27

Solving
-7 + 3x = 27

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 3x = 27 + 7

Combine like terms: -7 + 7 = 0
0 + 3x = 27 + 7
3x = 27 + 7

Combine like terms: 27 + 7 = 34
3x = 34

Divide each side by '3'.
x = 11.33333333

Simplifying
x = 11.33333333

See similar equations:

| 2x+29=300 | | 6n^2+48n+72=0 | | 28n^2=-96-183n | | 5a+56=(7)(8) | | 10x^2y= | | n(3)=n+12 | | 3x+4x=16-3x | | 4c/5=4 | | 3x^2+8x^2-15x-40=0 | | 6(x+5)-42=8 | | 33xy^5z^3= | | h=16t^2+400t | | 8(x+2)=(6x-7) | | sinx+cosx=6x | | 15(x+1)-5(10x+9)+2(5x+3)+4=0 | | 7z-9=3 | | 4/3=10/x | | -4p=44 | | 11-a=13 | | 2x+14=-28 | | 6(-6x+4)=-8(4x-6) | | -x-13+25=-3+52 | | 75x-2=-14 | | (12x+1)=(20x+19) | | 5(r-8)-4(6r-4)=-8r-8r | | 2x=5x+21-6 | | 3(1+11)= | | 5a^2+60a+180=0 | | 3x^2-18x-19=0 | | 2(1+x)=3(x+4) | | 9x+70=360 | | 2x(x-4)(x+8)=0 |

Equations solver categories